Pneumoconiosis and chronic bronchitis. Issue 6084 (13th August 1977) - Muir, D C; Burns, J; Jacobsen, M; Walton, W H
Abstract : Data from a major long-term epidemiological survey in the British coalmining industry were examined to determine whether bronchitis offered any protective action against the development of pneumoconiosis. No evidence of such an effect was found.